The Influence of Organizational Culture on Employee Performance With the Mediation of Psychological Capital and Employee Satisfaction in the Library and Archives Service in Central Kalimantan - Norol Aisyah; Roby Sambung; Rita Yuanita Toendan; Muhamad Ruzaini Abdi (Dinasti Review, 2025)
This study aims to examine the effect of organizational culture on employee performance with the mediation of psychological capital and employee satisfaction at the Department Library and Archives Office in Central Kalimantan. Using quantitative approach and SEM-PLS version 4.0 method, this study involved 75 respondents selected through purposive sampling. Data were collected through online questionnaire, namely Google Form and direct observation. The results of the study show that organizational culture has a positive and significant effect on psychological capital, employee satisfaction, and employee performance. Psychological capital and employee satisfaction also have a positive and significant effect on employee performance. Indirectly, organizational culture influences employee performance through these two variables as mediators.